Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Here is a tough integral. Does anyone have any clever ideas?. I have tried all sorts of things, but make no real headway.

$\displaystyle \int_{0}^{\infty}\frac{e^{-x^{2}}\sin^{2}(x)}{x^{2}}dx$

Would residues be a consideration with this one?.

Thanks all.

share|cite|improve this question
It's not pretty, but maybe Taylor expand $\sin^2 x / x^2$ about $x=0$, which will contain even powers only of $x$, and then use 27 here?: – Eric Angle Dec 18 '12 at 23:37

The answer is $$\int_0^\infty dx\,\frac{e^{-x^2}\sin^2 x}{x^2}=\frac{\pi}{2}\,{\rm erf}(1)-\frac{\sqrt{\pi}}{2e}(e-1).$$ Consider $$I(a)=\int_0^\infty dx\,\frac{e^{-ax^2}\sin^2 x}{x^2}$$ for which $$-I'(a)=\int_0^\infty dx\,e^{-ax^2}\sin^2 x.$$ This last integral can be done by expanding sine in terms of exponentials and completing the square in each term. The result is $$-I'(a)=\frac{\sqrt{\pi}}{16a}e^{-1/a}\left(e^{1/a}-1\right)$$ which can be anti-differentiated (I used Mathematica) in terms of the error function. As $a\to\infty$, $I(a)\to 0$, setting the constant of integration. Plugging in $a=1$ gives your answer.

share|cite|improve this answer
Thank you, Jonathon. This was one way I actually began, but got bogged down. Thank you. – Cody Dec 19 '12 at 11:25

Note that $$\dfrac{\sin^2(x)}{x^2} = \dfrac{1-\cos(2x)}{2x^2} = \dfrac{1 - \displaystyle \sum_{k=0}^{\infty} \dfrac{(-1)^k (2x)^{2k}}{(2k)!}}{2x^2} = \dfrac{\displaystyle \sum_{k=1}^{\infty} \dfrac{(-1)^{k-1} (2x)^{2k}}{(2k)!}}{2x^2} = \displaystyle \sum_{k=1}^{\infty} \dfrac{(-1)^{k-1} 2^{2k-1}x^{2k-2}}{(2k)!} = \displaystyle \sum_{k=0}^{\infty} \dfrac{(-1)^{k} 2^{2k+1}x^{2k}}{(2k+2)!}$$ \begin{align} \int_0^{\infty} \dfrac{\exp(-x^2)\sin^2(x)}{x^2} dx & = \displaystyle \sum_{k=0}^{\infty} \left(\dfrac{(-1)^{k} 2^{2k+1}}{(2k+2)!} \int_0^{\infty} x^{2k}\exp(-x^2) dx \right)\\ & = \displaystyle \sum_{k=0}^{\infty} \left(\dfrac{(-4)^{k}}{(2k+2)!} \Gamma \left(k + \dfrac12 \right) \right) \end{align} which is same as what Jonathan has obtained.

share|cite|improve this answer
Thank you, Marvis. I tried series as well. Of course, got bogged down and stuck. Using the double identity was a clever idea. I like and appreciate both methods. I hate to have to choose. – Cody Dec 19 '12 at 11:27

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.